2005
DOI: 10.1016/s1015-9584(09)60346-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vacuum-assisted Closure on Wound Microcirculation: An Experimental Study

Abstract: By increasing capillary calibre and blood volume and by stimulating angiogenesis, VAC could improve blood circulation in wounds. By narrowing endothelial spaces and by restoring the integrity of capillary basement membranes, VAC could decrease the permeability of blood vessels and wound oedema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
169
2
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(188 citation statements)
references
References 9 publications
6
169
2
11
Order By: Relevance
“…Further, it narrowed endothelial spaces and restored the integrity of capillary basement membranes causing a decrease in the permeability of blood vessels and wound oedema by removing excessive fluid from the wound bed. 6 An increased rate of granulation tissue formation was also shown to occur with NPWT application.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Further, it narrowed endothelial spaces and restored the integrity of capillary basement membranes causing a decrease in the permeability of blood vessels and wound oedema by removing excessive fluid from the wound bed. 6 An increased rate of granulation tissue formation was also shown to occur with NPWT application.…”
Section: Discussionmentioning
confidence: 97%
“…[6][7][8][9][10][11][12] In an experimental study conducted on rabbits, it was found that NPWT increased the blood circulation in the wounds by increasing the capillary calibre and blood volume and by stimulating angiogenesis. Further, it narrowed endothelial spaces and restored the integrity of capillary basement membranes causing a decrease in the permeability of blood vessels and wound oedema by removing excessive fluid from the wound bed.…”
Section: Discussionmentioning
confidence: 99%
“…9,21,22,20 This is due to narrowing of endothelial spaces with restoration of integrity of capillary basement membranes and increasing number and diameter of the capillaries that are formed. 23 However, the effect of vacuum-assisted closure on reduction and prevention of infection has not been established conclusively. 20 A study undertaken by…”
Section: Discussionmentioning
confidence: 99%
“…According to the second theory, it is estimated that angiogenesis and tissue growth are stimulated and these processes give rise to cell proliferation as a result of mechanical tissue stress. The final theory is that vacuum effect removes the protease molecules which constitute an important negative factor against wound healing and bacterial load decreases following this event [12][13][14][15]. Therefore, it is intended to produce an alive wound bed which is suitable for subsequent soft tissue reconstructions.…”
Section: Discussionmentioning
confidence: 99%